The Influence of Perceived Organizational Support on Task Performance Post-Transfer: A Systematic Review - Khoiroh, Muhimatul; Drahen Soeling, Pantius (International Journal Labs, 2025)
Public sector employee transfers often present challenges that can hinder individual performance and organizational effectiveness. This study conducts a systematic literature review to examine how perceived organizational support (POS) affects task performance following such transfers. Employing a structured search and thematic content analysis, 15 peer-reviewed studies from 2010 to 2025 were selected based on inclusion criteria emphasizing public sector relevance, POS, and task performance. The findings consistently show that POS positively influences task performance by fostering affective organizational commitment, psychological empowerment, adaptability, and motivation, which buffer the disruptive effects of relocation. The study reveals key mediators including job satisfaction, relational energy, and training transfer, as well as moderators such as perceived organizational competence (POC), employee adaptability, and the alignment between expected and received support. Unlike previous research that focused broadly on POS across sectors, this review offers a comparative perspective that highlights contextual variations across cultures, organizational structures, and transfer scenarios. The implications are twofold: for researchers, it identifies unexplored areas such as digital HR systems and longitudinal effects of POS in hybrid environments; for practitioners, it emphasizes the importance of strategic, tailored support systems to ensure smooth transitions and sustained performance. This review advances the organizational support literature by deepening understanding of the mechanisms and boundary conditions that shape the effectiveness of POS in public sector mobility.